Phosphorus flow analysis data.xlsx - Mnthambala, Frank (Cranfield University, 2021)
The P flow model for Malawi was produced using these data. The data was from the year 2016.
Keywords: P flow'; 'Circular economy'; 'Organic waste management'; 'organic fertilizer'; 'Agricultural Land Management'